Antenna toolkit / Joseph J. Carr. - Carr, Joseph J. (Newnes, 2001)
Carr covers basic topics such as radio signals on the move and wires and connections, and looks at a variety of different antenna types. The accompanying CD-ROM includes a freeware HF propagation predictor and a directory of equipment suppliers.